2007
DOI: 10.1021/ja073206+
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Water Photooxidation Reaction at Atomically Flat TiO2 (Rutile) (110) and (100) Surfaces:  Dependence on Solution pH

Abstract: The mechanism of water photooxidation reaction at atomically flat n-TiO(2) (rutile) surfaces was investigated in aqueous solutions of various pH values, using photoluminescence (PL) measurements. The PL bands, which peaked at around 810 and 840 nm for the (110) and (100) surfaces, respectively, were assigned to radiative transitions between conduction-band electrons and surface-trapped holes (STH), [Ti-O=Ti(2)](s)+, formed at triply coordinated (normal) O atoms at the surface lattice. The PL intensity (I(PL)) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
345
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(382 citation statements)
references
References 89 publications
33
345
2
2
Order By: Relevance
“…Third, literature reported that amorphous metal oxide sample has higher amount of randomly oriented bonds and higher structural flexibility relative to its crystalline counterpart, which translates to the formation of higher amount of surface unsaturated sites for facile reactant adsorption 9. In such metal phosphide, the highly electronegative P atoms can draw electron from metal atoms and act as proton carrier, thus contributing towards enhanced electrocatalytic activity 10. More significant is the fact that our XPS results above do indicate strong electronic interaction between the crystalline CoP and amorphous CoOx phases, which led to the favorable modification in the electronic structure and can lower the free energy for adsorption of intermediates, therefore enhancing the catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Third, literature reported that amorphous metal oxide sample has higher amount of randomly oriented bonds and higher structural flexibility relative to its crystalline counterpart, which translates to the formation of higher amount of surface unsaturated sites for facile reactant adsorption 9. In such metal phosphide, the highly electronegative P atoms can draw electron from metal atoms and act as proton carrier, thus contributing towards enhanced electrocatalytic activity 10. More significant is the fact that our XPS results above do indicate strong electronic interaction between the crystalline CoP and amorphous CoOx phases, which led to the favorable modification in the electronic structure and can lower the free energy for adsorption of intermediates, therefore enhancing the catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…31 In this mechanism, the OH cleavage in an H 2 O molecule corresponds to the deprotonation from the protonated hydroxy group ( + OH 2 ) on the TiO 2 surface. Thus, this OH cleavage would not be the rate-determining step.…”
Section: ç Reaction Mechanismmentioning
confidence: 99%
“…Under the basic conditions, it was proposed that a deprotonated terminal TiO ¹ site traps a photoformed hole to become a surface oxygen radical species. 31 In the hydroxylation, this oxygen species reacts with an H 2 O molecule through the O H bond cleavage in the H 2 O molecule and produces a hydroxyl radical (Scheme 8a). This reaction step should proceed with the isotopic effect of D 2 O, consistent with the results in the basic condition (Entries 5 and 6).…”
Section: ç Reaction Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Moreover, it has been known that there exists a lot of lattice changes during TiO 2 photocatalysis. [13][14][15] The urgency for the mechanism drives cutting-edge researches to the relationship between the lattice changes and photocatalytic activity of TiO 2 . In our previous work, 16 we studied the photocatalytic process in an atomic scale by using HRTEM.…”
Section: Introductionmentioning
confidence: 99%